Try NerdPal! Our new app on iOS and Android

# Solve the inequality $\frac{\left(x+2\right)\left(x+2\right)}{6}\geq \frac{x}{3}+\frac{1}{2}$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Videos

$x\geq -1$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

${\frac{\left(x+2\right)\left(x+2\right)}{6}}\geq {\frac{x}{3}+\frac{1}{2}}$

Specify the solving method

1

When multiplying two powers that have the same base ($x+2$), you can add the exponents

$\frac{\left(x+2\right)^2}{6}\geq \frac{x}{3}+\frac{1}{2}$
2

Move everything to the left hand side of the equation

$\frac{\left(x+2\right)^2}{6}+\frac{-x}{3}-\frac{1}{2}\geq 0$

Learn how to solve one-variable linear inequalities problems step by step online.

$\frac{\left(x+2\right)^2}{6}\geq \frac{x}{3}+\frac{1}{2}$

Learn how to solve one-variable linear inequalities problems step by step online. Solve the inequality ((x+2)(x+2))/6>=x/3+1/2. When multiplying two powers that have the same base (x+2), you can add the exponents. Move everything to the left hand side of the equation. The least common multiple (LCM) of a sum of algebraic fractions consists of the product of the common factors with the greatest exponent, and the uncommon factors. Obtained the least common multiple, we place the LCM as the denominator of each fraction and in the numerator of each fraction we add the factors that we need to complete.

$x\geq -1$
SnapXam A2

### beta Got a different answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

${\frac{\left(x+2\right)\left(x+2\right)}{6}}\geq {\frac{x}{3}+\frac{1}{2}}$